Massive Juvenile Psammomatoid Ossifying Fibroma in the Mandible With a Complex Clinical Course: Case Report and Literature Review. Issue 3 (September 2022) - Silver, Eric; Yusupov, Steve; Lam, Lydia; Schultz, Kathleen; Hoffman, David
The juvenile ossifying fibroma is a rare subset of the benign ossifying fibroma. These tumors have an aggressive behavior and often cause severe destruction of bone and surrounding tissue. JOF can be separated into the juvenile trabecular ossifying fibroma and juvenile psammomatoid ossifying fibroma. In this article, we present a case of an 18 year old male who presented with a rapidly growing massive tumor originating in the right mandible that caused severe local destruction. Due to the size of the tumor, the patient had impairment in many activities of daily living. Pre-operative management was further complicated due to the vascular nature of the tumor which resulted in spontaneous bleeding. The tumor was successfully resected and final pathology revealed a diagnosis of juvenile psammomatoid ossifying fibroma. In this article, we describe treatment of a debilitating mandibular tumor and provide recommendations for other clinicians who encounter similar cases. Additionally, the demographics and histopathological features of the juvenile ossifying fibroma and its subtypes are described.